A randomized controlled trial of coordination exercise on cognitive function in obese adolescents. (January 2018) - Liu, Jen-Hao; Alderman, Brandon L.; Song, Tai-Fen; Chen, Feng-Tzu; Hung, Tsung-Min; Chang, Yu-Kai
Abstract: Objective: Whether the beneficial effect of coordination exercise on executive function extends to obese adolescents remains understudied and no study to date has examined the effect of exercise on food-cue related executive function. The aim of this randomized controlled trial was to investigate the effects of a coordination exercise program on executive function in obese adolescents. Design: A randomized controlled trial. Methods: Eighty obese adolescents were randomly assigned to a 12-week coordination exercise program or a waitlist control group and data from 70 participants (n = 35 for each group) were analyzed. The after-school exercise program involving a multifaceted moderate-intensity jump rope program performed twice weekly for 75 min per session. The primary outcome of normal and food-cue related Stroop task performance was assessed prior to and following the intervention. Secondary outcomes included physical fitness and body mass index (BMI). Results: The coordination exercise intervention improved both normal and food-cue related cognitive function. Similar beneficial effects were also found for physical fitness and BMI. However, pre-to-post intervention change in physical fitness and BMI did not significantly mediate enhanced cognitive and executive function performance. Conclusion: In obese adolescents, a coordination exercise intervention is an effective approach to improve multiple aspects of cognitive function while enhancing physical fitness and reducing obesity. These findings also suggest a possible role of cognitive inhibition in exercise-associated weight loss among obese adolescents. Highlights: Effect of the coordination exercise on executive function in obese adolescent remains understudied. The multifaceted coordination exercise program was effective at improving physical fitness and reducing obesity. The program also benefits to enhance both general and obesity-related executive function among obese adolescents. There is a possible role of obesity-related inhibition in exercise-associated weight loss among obese adolescents.